Nucleotide-rich yeast extract fed to broiler chickens challenged with Eimeria: impact on growth performance, jejunal histomorphology, immune system, and apparent retention of dietary components and caloric efficiency1. (25th April 2019) - Leung, H; Patterson, R; Barta, J R; Karrow, N; Kiarie, E
ABSTRACT: Nucleotide-rich yeast extract (YN) was investigated for its effects on growth performance, jejunal histomorphology and mucosal immunoglobulin A (IgA), immune organs weight and apparent retention (AR) of components in broiler chickens challenged with Eimeria . A total of 336 day-old male chicks (Ross x Ross 708) were placed in floor pens and provided a corn-soybean meal-based diet without or with YN (500 g/mt) (n = 14). On day 10, 7 replicates per diet were orally administered with 1 mL of sporulated E. acervulina and E. maxima oocysts and the rest (non-challenged control) administered equivalent distilled water creating a 2 × 2 factorial arrangement for the post-challenge period (day 11 to 35). Feed intake (FI), BWG, and FCR responses were measured in pre- and post-challenge periods. Excreta samples were collected on day 14 to 17 and 31 to 34 for oocyst count and AR of components, respectively. On day 15 and 35, 5 birds/pen were necropsied for intestinal samples. Spleen, bursa, and thymus weights were also recorded at both time points and breast yield on day 35. Diet had no effect ( P > 0.05) on pre-challenge growth performance. Interaction ( P = 0.046) between Eimeria and YN on FI was such that Eimeria challenge increased FI (day 11 to 35) in non-YN birds. There was no interaction ( P > 0.05) between Eimeria and YN on other post-challenge responses. Eimeria reduced ( P < 0.05) BWG, FCR, caloric efficiency, day 15 jejunal villi height and IgA concentration, and increased ( P < 0.01) day 15 spleen weight. On day 35, YN increased bursa weight (1.57 vs. 1.78 mg/g BW, P = 0.04). There was a tendency for an interaction effect ( P = 0.09) on day 35 thymus weight, such that in challenged birds, YN fed birds tended to have a lighter thymus relative to non-YN fed birds. In conclusions, independent of Eimeria challenge, supplemental YN had no effect on growth performance, caloric efficiency, and intestinal function but increased immune organ weights.